Review of Laboraotory and Clinical Studies of Olestra, a Nonabsorbable Lipid - Carolyn M Bergholz; Ronald J Jandacek; Alan BR Thomson (Canadian Journal of Gastroenterology)
The classical understanding of fat digestion and absorption is provided as background for a review of research on olestra, a triglyceride-derived lipid that is not digested or absorbed from the intestinal lumen. Olestra (formerly ‘sucrose polyester’) is the generic name proposed for the mixture of the hexa, hepta and octa long chain fatty acid esters of sucrose. Olestra has the physical properties of fat and can therefore function as a zero calorie fat replacement in foods. The fate and effects of olestra in the gastrointestinal tract have been extensively investigated in animals and humans. Evidence from a variety of studies shows that olestra is not digested or absorbed and is not metabolized by colonic microflora. Feeding studies in five different species of animals show that olestra is nontoxic and noncarcinogenic, and causes no morphological changes in any tissues of the gastrointestinal tract. Consumption of olestra foods does not alter gastric emptying, transit through the small and large bowel, bile acid physiology, bowel function, or fecal pH, water and electrolytes. Nutritional research shows no effect on absorption of macronutrients. Highly lipophilic materials such as cholesterol and vitamin E have the potential to partition into olestra, thereby decreasing their solubilization in intestinal micelles and subsequent absorption. Clinical research shows a modest reduction in serum cholesterol and vitamin E levels. The effect on vitamin E absorption can be offset by supplementation of olestra with vitamin E. The status of vitamins D and K and absorption of lipophilic drugs are not altered by daily consumption of 18 g olestra. Although serum retinol levels are not reduced, additional research is focusing on effects of olestra on hepatic stores of vitamin A to assess the appropriateness of supplementation. Using olestra to reduce the amount of fat in high fat foods, without affecting other nutrient, should contribute to a diet lower in energy from fat and higher in energy from carbohydrate.